Feminist Ethics and Social and Political Philosophy: Theorizing the Non-Ideal
XXVI, 301 p.
Keywords: Feminist Ethics and Social and Political Philosophy: Theorizing the Non-Ideal is a collection of feminist essays that self-consciously develop non-idealizing approaches to either ethics or social and political philosophy (or both). Characterizing feminist ethics and social and political philosophy as marked by a tendency to be non-idealizing serves to thematize the volume, while still allowing the essays to be diverse enough to constitute a representation of current work in the fields of feminist ethics and social and political philosophy. Each of the essays either serves as an instance of work that is rooted in actual, non-ideal conditions, and that, as such, is able to consider any of the many questions relevant to subordinated people; or reflects theoretically on the significance of non-idealizing as an approach to feminist ethics or social and political philosophy. The volume will be of interest to feminist scholars from all disciplines, to academics who are ethicists and political philosophers as well as to graduate students.